PENCEGAHAN KELAHIRAN STUNTING DENGAN PENINGKATAN PENGETAHUAN RISIKO PERNIKAHAN DINI DI DESA BANDARASRI KABUPATEN MOJOKERTO - Isfatayati, Nur; Santosa, Bernadheta Donabella Ega; Utari, Komang Mega Ilda; Putricia, Andini Mutiara; Hartono, Verina Dewanti; Fahrudin, Tresna Maulana (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Jakarta, 2022)
Stunting is one of the nutritional problems in children that is of global concern, especially in lower-middle-income countries. According to the World Health Organization (WHO), stunting is a developmental disorder in children caused by poor nutrition, repeated infections, and inadequate psychosocial stimulation. In 2021, the stunting prevalence rate in Mojokerto Regency reached 27.4%. This raises many concerns about reducing stunting rates. The purpose of community service in the form of the Thematic Student Community Service - Independent Learning-Independent Campus (MBKM) program is to increase public knowledge about the risks of early marriage as an effort to prevent stunting. The method used is socialization where participants consisted of 37 people between 13 and 20 years of age who were residents of Bandarasri Village. Based on the survey results, the percentage obtained shows a decrease in the number on the indicator